2019
DOI: 10.1002/spp2.1255
|View full text |Cite
|
Sign up to set email alerts
|

Cambrian rhynchonelliform nisusioid brachiopods: phylogeny and distribution

Abstract: A comprehensive review and phylogenetic analysis of genera and species presently assigned to the rhynchonelliform superfamily Nisusioidea and family Nisusiidae suggests that this short‐lived but important group of brachiopods first appeared in peri‐Gondwana during the second half of the Cambrian Series 2, before going extinct by the end of Drumian times. Nisusiides achieved their maximum morphological disparity and geographical distribution during the Wuliuan Age, and Laurentia was probably the major centre of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(41 citation statements)
references
References 29 publications
0
41
0
Order By: Relevance
“…To date, four of the five nisusiid species documented from the unnamed Cambrian Series 2, including Eoconcha austini Cooper, 1951, Nisusia festinata (Billings, 1861), Nisusia ancauchensis Benedetto and Foglia, 2012, and Nisusia fulleri described herein, are from Laurentia, suggesting that this continent was probably the major center of early Cambrian nisusiid dispersal (Holmer et al, 2019). Nisusia fulleri is closely similar to the type species N. festinata, with the latter being spinocostellate and appears to have costellae of more even size and a narrower, deeper sulcus.…”
Section: Systematic Paleontologymentioning
confidence: 94%
See 2 more Smart Citations
“…To date, four of the five nisusiid species documented from the unnamed Cambrian Series 2, including Eoconcha austini Cooper, 1951, Nisusia festinata (Billings, 1861), Nisusia ancauchensis Benedetto and Foglia, 2012, and Nisusia fulleri described herein, are from Laurentia, suggesting that this continent was probably the major center of early Cambrian nisusiid dispersal (Holmer et al, 2019). Nisusia fulleri is closely similar to the type species N. festinata, with the latter being spinocostellate and appears to have costellae of more even size and a narrower, deeper sulcus.…”
Section: Systematic Paleontologymentioning
confidence: 94%
“…Remarks.-Nisusia has most commonly been regarded as a poorly defined 'waste basket' taxon, due to the fact that the morphology of many species described in the first half of the previous century are inadequately known. However, Holmer et al, (2019) recently reviewed the phylogeny and distribution of nisusioid brachiopods and restricted Nisusia to species provided with radiating costellae bearing hollow spines. Holmer et al (2019) also suggested that most of the taxa (mainly from Laurentia) from the lower Cambrian (unnamed stages 3-4) that have been assigned to Nisusia, belong neither to Nisusia nor to Nisusioidea, and presently only 19 taxa, plus one described under open nomenclature, can be assigned to Nisusia with some degree of confidence, whereas the generic affinities of five more species require further study.…”
Section: Systematic Paleontologymentioning
confidence: 99%
See 1 more Smart Citation
“…Remarks.-Nisusia liantuoensis was first recorded from the Shipai Formation of Liantuo, Yichang City, South China (Zeng, 1987). Spinose ornament is unclear in Zeng (1987), hence Holmer et al (2019) suggested this species designation may be questionable. Specimens from the Shipai Formation at Xiachazhuang section bear a strong resemblance to N. liantuoensis from Liantuo (shell subequally biconvex, semicircular in outline; ventral umbo strongly raised; ventral interarea high; the maximum height of the ventral valve at apex), and the new material from Xiachazhuang section also preserves the characteristic hollow spines of Nisusia.…”
Section: Linnarssonia Sapushanensismentioning
confidence: 99%
“…Nisusia liantuoensis was first recorded from the Shipai Formation of Liantuo, Yichang City, South China (Zeng, 1987). Spinose ornament is unclear in Zeng (1987), hence Holmer et al (2019) suggested this species designation may be questionable. Specimens from the Shipai Formation at Xiachazhuang section bear a strong resemblance to N .…”
Section: Systematic Paleontologymentioning
confidence: 99%